The Impact of Intellectual Capital on Organizational Performance in the Banking Sector of Bangladesh - Bablu Kumar Dhar (Universiti Sains Islam Malaysia, 2024)
The aim of the research is to investigate the impact of intellectual capital on organizational performance in the banking sector of Bangladesh. Utilizing intellectual capital becomes mandatory for competitive advantage and better performance. This study evaluated the moderating effect of environmental turbulence and motivation on the dimensions of intellectual capital (human capital, structural capital, and relational capital) and organizational performance through knowledge management. This research was conducted using a quantitative approach. The questionnaires were designed to collect data from the sample of 354 managers from a population of 4,498 managers for the 30 banks listed on the Dhaka Stock Exchange of Bangladesh. A total of 286 responses were usable and used for subsequent analysis. The statistical package of social sciences (SPSS) program was used for the factor analysis, reliability analysis, and descriptive statistical analysis. The AMOS program was used for structural equation modelling as well as to examine the research hypotheses. The results showed that knowledge management has a significant mediation effect, and that environmental turbulence and motivational effect have a significant moderating effect between intellectual capital and organizational performance in the banking sector of Bangladesh. This study has added to the body of knowledge in determining the moderating effect of environmental turbulence and motivational effect on intellectual capital and organizational performance through knowledge management, by extending the theory of intellectual capital, the resource-based view, and contingency theory.